A modular algorithm for computing the exponential solutions of a linear differential operator - Cluzeau, Thomas; van Hoeij, Mark (Journal of symbolic computation, 2004)
We present a new algorithm for computing exponential solutions of differential operators with rational function coefficients. We use a combination of local and modular computations, which allows us to reduce the number of possibilities in the combinatorial part of the algorithm. We also show how unnecessarily large algebraic extensions of the constants can be avoided in the algorithm.